2010
DOI: 10.1590/s0034-89102010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation and psychometric properties of Brazilian Need for Recovery Scale

Abstract: OBJECTIVE:To translate the Need for Recovery Scale (NFR) into Brazilian Portuguese and culturally adapt it and assess the stability, internal consistency and convergent validity of the Brazilian scale among industrial workers. METHODS:The translation process followed the guidelines for cultural adaptation of questionnaires including the steps of translation, synthesis, back translation, expert committee review, and pre-testing. The Brazilian Portuguese NFR, fi nal version (Br-NFR) was assessed for stability (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 20 publications
0
39
0
4
Order By: Relevance
“…the Nordic musculoskeletal questionnaire 19 , the work ability index 20 , and the need for recovery scale (NRS) 7 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…the Nordic musculoskeletal questionnaire 19 , the work ability index 20 , and the need for recovery scale (NRS) 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Walsh et al 5 demonstrated that the analysis of functional deficits is fundamental, considering the impact of work-related musculoskeletal disorders (WRMD) on the worker's abilities and health. As an example, Sluiter et al 6 and Moriguchi et al 7 demonstrated that the evaluation of work-induced fatigue might be interesting to determine the exposure to physical and mental demands in the occupational environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The workers answered a questionnaire containing demographic data (age, gender, educational level and marital status), occupational data (job function) and aspects of everyday life (housekeeping activities, smoking and physical activity practice) as well as the NFR 10 . The two occupational sectors in which participants worked were ergonomically assessed by an experienced physical therapist according to the Ergonomic Workplace Analysis (EWA) protocol, which was proposed by the Finnish Institute of Occupational Health 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Considering the diversity of existing occupational situations and the possible risk factors in each situation, tools that help identify ergonomic intervention priorities can be useful for health professionals involved in work-related disease control 9 since the earlier the identification, the more effective preventive interventions may be. A useful tool for such identification is the Need for Recovery Scale (NFR) 10 , which has been used to assess work-induced fatigue. It considers fatigue as a result of exposure to physical and mental demands imposed by work 11,12 .…”
Section: Introductionmentioning
confidence: 99%